Evaluation of Sports Recreation and Sports TourismDevelopmentProgramin Mandeh Integrated Marine Area by the Department of Youth Sportsand Tourism, Pesisir Selatan Regency - Hendro Putra Mardani; Anton Komaini; Wilda Welis (JURNAL STAMINA, 2018)
The problem in this study is that recreational sports and tourism sports have not developed optimally. This is suspected because the development program given to the Integrated Marine Protected Area is not running optimally, so that the Sports Recreation and Sports Tourism that the Community hopes or the Mandeh Region Manager has not achieved. The purpose of this study is to evaluate the development of Sports Recreation and Sports Tourism Integrated Mandeh Marine Areas. The method in this study uses descriptive qualitative research using the CIPP method (Context, Input, Process, Product). The data of this study were obtained through observation, interviews and documentation. The results of the study were found in terms of the context of the objectives of the recreational sports and tourism sports development program, namely 1. for sports achievements 2. to attract foreign tourist visits so that they come to Mandeh Integrated Marine Zone. Supporting factors support the success of recreational sports and tourism sports development programs in mandeh areas, namely 1. funds 2. natural resources in the integrated maritime region must be mandatory and support from the nagari or sub-district community. Obstacles are funds. In terms of input This year there is the Mandeh Enchantment Festival. In terms of the process of preparing for the implementation of recreational sports and tourism sports programs in the Integrated Marine Maritime Region in October there is an integrated marine maritime festival event. Product aspect for the development of recreational sports is still undeveloped in the Mandeh Integrated MarineArea. ABSTRAK Masalah dalam penelitian ini adalah olahraga rekreasi dan olahraga pariwisata belum berkembang maksimal. Hal ini di duga karena program pengembangan yang diberikan kepada Kawasan Bahari Terpadu Mandeh kurang berjalan secara maksimal, sehingga Olahraga Rekreasi dan Olahraga Pariwisata yang di harapkan Masyarakat atau Pengelola Kawasan Mandeh belum tercapai. Tujuan penelitian ini adalah untuk mengevaluasi program pengembangan Olahraga Rekreasi dan Olahraga Pariwisata Kawasan Bahari Terpadu Mandeh. Metode dalam penelitian ini menggunaan penelitian deskriptif kualitatif dengan menggunakan metode CIPP (Context, Input, Process, Product). Data penelitian ini diperoleh melalui observasi, wawancara dan dokumentasi. Hasil penelitian ditemukan dari segi context tujuan program pengembangan olahraga rekreasi dan olahraga pariwisata yaitu 1. untuk prestasi olahraga 2. untuk menarik kunjugan wisatawan asing supaya ramai datang ke Kawasan Bahari Terpadu Mandeh. Faktor pendukung menunjang keberhasilan program pengembangan olahraga rekreasi dan olahraga pariwisata di kawasan mandeh yaitu 1. dana 2. sumber daya alam yang ada di kawasan bahari terpadu mandeh kemudiaan adanya dukungan dari masyarakat nagari atau camat. Hambatan adalah dana. Dari segi input Tahun ini ada Festival Pesona Mandeh. Segi proses Persiapan pelaksanaan program olahraga rekreasi dan olahraga pariwisata di Kawasan Bahari Terpadu Mandeh di bulan oktober ada even festival pesona bahari terpadu mandeh. Segi Product pengembangan olahraga rekreasi masih belum berkembang di Kawasan Bahari TerpaduMandeh.